Robust time resource allocation and multi-user selection algorithm for data and energy integrated communication network - Jiayu YANG; Jie HU; Supeng LENG; Kun YANG (物联网学报)
In the existing research on resource allocation in wireless energy and data transmission,the impact of battery capacity on throughput under multi-user scenarios is not considered.A robust resource allocation algorithm was proposed to optimize throughput and solve the problem that a single model could not reasonably allocate resources in real world network scenarios due to large differences in battery capacity.In addition,a connection between multi-user selection and slot allocation was found,and a joint optimization algorithm of multi-user selection and slot allocation under the constraint of power was proposed.The simulation results show that the proposed algorithm has better throughput performance and is more suitable for wireless data and energy transmission network.